Matching supplementary motor area-primary motor cortex paired transcranial magnetic stimulation improves motor dysfunction in Parkinson’s disease: a single-center, double-blind randomized controlled clinical trial protocol - Tang, Xiaoshun; Huang, Zhexue; Zhu, Guangyue; Liang, Haoyuan; Sun, Hui; Zhang, Yu; Tan, Yalin; Cui, Minglong; Gong, Haiyan; Wang, Xijin; Chen, Yu-Hui (Frontiers in Aging Neuroscience, 2024)
Non-invasive neuroregulation techniques have been demonstrated to improve somecertain motor symptoms ofin Parkinson's disease( (PD).). However, the currently employed regulatory techniques primarily concentrate on stimulating single target points, neglecting the functional regulation of networks and circuits. The supplementary motor area (SMA) has a significant value in motor control, and its functionality is often impaired in patients with PD. The matching SMA-primary motor cortex( (M1)) paired transcranial magnetic stimulation (TMS) treatment protocol, which benefits patients by modulating the sequential and functional connectionconnections between the SMA and primary motor cortex (M1),, was elucidated in this study.This was a single-center, double-blind, randomized, controlled clinical trial. We recruited 78 subjects and allocated them in a 1:1 ratio by stratified randomization into the paired stimulation (n = 39) and conventional stimulation groups (n = 39). Every patientsEach patient underwent three weeks of matching SMA-M1 paired TMS or sham -paired stimulation.Evaluations were conducted on theThe subjects prior to thewere evaluated before treatment initiation of treatment, three weeks into the intervention, and three months after the cessation of therapy. The primary outcome measure ofin this study was the UPDRSⅢ,Unified Parkinson's Disease Rating Scale III, and the secondary outcome measures included non-motor functional assessment (NMSS),, quality of life (PDQParkinson's Disease Questionnaire -39), and objective assessments (electromyography and fNIRSfunctional near-infrared spectroscopy).Discussion: Clinical protocols aimed at single targets viausing non-invasive neuroregulation techniques often improve only one function. Emphasizing the circuit and network regulation ofin PD is an important direction for enhancing the effectiveness of TMS rehabilitation. Pairing the regulation of cortical circuits may be a significant potential treatment method for treating PD. As a crucial node in motor control, the SMA has direct fiber connections with basal ganglia circuits and complex fiber connections with M1, which are responsible for motor execution. SMA regulation may indirectly regulate the function of basal ganglia circuits. ThusTherefore, the developed cortical pairing stimulation pattern can reshape the flow of control of information flow from the SMA to M1.